Fundamentos de uma educação Ética e Tecnológica - Silva, Guery Tã Baute e; Mungulume, Manuel João (Faculdade de Filosofia e Ciências, 2019)
The problems of contemporary societies are becoming increasingly complex so that many of them cannot be solved by prevailing technical education. This work uses a bibliographic revision to transport the technological problem to the level of moral conscience, in order to build a responsible social level in relation to the problems brought by the technique. For this, we sought in this work primarily to explain the development for a technical education and departmentalization based on the fragmentation of knowledge. It was then demonstrated the impact of technologies on social and environmental life in which is evident the harm that humans do the earth with pollution and their way of life. Then the work presents the overcoming of technique by nature, where the globalization of the economy endangers not only nature, but also the philosophical link between nature and man. Finally, this paper discusses the emergence of liberating “greening” thinking to solve the complex problems of contemporary society. As a basis the educational perspectives of Edgar Morin (2002) and Paulo Freire (1999) are used. Submissão : 2019- 03-23 Aceite: 2019-05-01